Assessing early childhood physical literacy score in Indonesia: exploring the correlation between teacher perception, active teacher involvement, and school status - Aryati Aryati; Elindra Yetti; Tuty Tarwiyah; Mohamad Syarif Sumantri; Juriana Juriana; Evania Yafie; Sandi Prayudho (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to determine the relationship between teachers' perspectives, active teacher involvement and school status in relation to children's physical literacy in Indonesia. This research is a correlational study with a quantitative approach. The sample was taken by purposive sampling. The sample includes 100 teachers from 100 schools accredited A, B, and C. The physical literacy instrument for early childhood uses the Pre-PLAY which consists of three domains, namely physical competence, coordinated movement and motivation and enjoyment. Data analysis in this study is descriptive analysis using linear analysis in the form of validity and reliability tests. The results showed that there is a significant positive relationship between teachers' perception and their involvement with early childhood physical literacy, with significance values of 0.001 and 0.000, meanwhile, there is no significant relationship between school accreditation status and early childhood physical literacy, with a significance value of 0.096. It can be concluded that physical literacy is important to be applied to support the development of young children. Teachers play a fundamental role in implementing the concept of physical literacy in children a teacher's understanding of physical literacy is crucial because it can help children become more active, and their active engagement in applying this concept is equally important as it can enhance physical activity.